Passion in the desert: a qualitative exploration of recreational motivations and challenges for hunting and camping in Saudi Arabia - Homoud Mohammed Nawi Alanazi (Cogent Social Sciences)
Amidst the vast landscapes of Saudi Arabia lies a rich tapestry of recreational pursuits, with hunting and camping at its core. However, a comprehensive understanding of the motivations and challenges associated with these traditional activities remains scant. The primary objective of this study was to explore the driving factors behind individuals’ engagement in hunting and camping as recreational pursuits and to identify the challenges they encounter. Adopting a qualitative research design, 43 male participants, aged 20 to more than 50, were purposively selected and interviewed using a semi-structured format. The instrument encompassed two main sections: demographic details and four key interview questions. Thematic analysis was employed to interpret the data. Findings from this study illuminated a diverse array of motivations driving individuals towards hunting and camping activities in Saudi Arabia. These motivations span from cultural heritage, an escape from urbanization, adventure, and social bonding, to government promotions and spiritual connections. Conversely, participants face multifaceted challenges, including environmental unpredictability, bureaucratic complexities, technological intrusions, mental challenges, safety concerns, and financial constraints. Delving into these intricate dynamics, the study offers an enriched understanding of recreational motivations and their challenges in the Saudi context, bridging a notable academic gap and paving the way for future research and informed policy-making.